Answer:
hope that helps
Step-by-step explanation:
3x^2+2xy+y2=2
6x + 2y + 2xy' + 2yy' = 0
x=1 ==> y=-1
6(1) + 2(-1) + 2(1)y' + 2(-1)y' = 0
6 - 2 + 2y' - 2y' = 0
4 = 0
(e) undefined
The graph is an ellipse. At (1,-1) there is a vertical tangent
Answer:
. The slope of the line indicates that test score and the time spent watching tv are negatively correlated
Answer:
(5a+b)⋅(5a−b)
Step-by-step explanation:
Changes made to your input should not affect the solution:
(1): "b2" was replaced by "b^2". 1 more similar replacement(s).
STEP
1
:
Equation at the end of step 1
52a2 - b2
STEP
2
:
Trying to factor as a Difference of Squares
2.1 Factoring: 25a2-b2
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
Proof : (A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
Note : AB = BA is the commutative property of multiplication.
Note : - AB + AB equals zero and is therefore eliminated from the expression.
Check : 25 is the square of 5
Check : a2 is the square of a1
Check : b2 is the square of b1
Factorization is : (5a + b) • (5a - b)
Answer:
0
Step-by-step explanation:
2 + 2 = 4 and then 4 - 4 = 0
Answer:
literally at this point i think its (D)
Step-by-step explanation: